A Great Step Forward. Lithic Raw Material Procurement and Management among Palaeolithic Hunter-Gatherers in the Basque Crossroads. (2020) - , Maite García-Rojas, Eder Dominguez-Ballesteros, Alejandro Prieto, Aitor Calvo, Aitor Sánchez, Andoni Tarriño; Arrizabalaga, Alvaro
No abstract available